Dishevelled-1 Regulates Microtubule Stability: A New Function Mediated by Glycogen Synthase Kinase-3β - Krylova, Olga (The Rockefeller University Press, 2000)
Dishevelled has been implicated in the regulation of cell fate decisions, cell polarity, and neuronal function. However, the mechanism of Dishevelled action remains poorly understood. Here we examine the cellular localization and function of the mouse Dishevelled protein, DVL-1. Endogenous DVL-1 colocalizes with axonal microtubules and sediments with brain microtubules. Expression of DVL-1 protects stable microtubules from depolymerization by nocodazole in both dividing cells and differentiated neuroblastoma cells. Deletion analyses reveal that the PDZ domain, but not the DEP domain, of DVL-1 is required for microtubule stabilization. The microtubule stabilizing function of DVL-1 is mimicked by lithium-mediated inhibition of glycogen synthase kinase-3β (GSK-3β) and blocked by expression of GSK-3β. These findings suggest that DVL-1, through GSK-3β, can regulate microtubule dynamics. This new function of DVL-1 in controlling microtubule stability may have important implications for Dishevelled proteins in regulating cell polarity.